2017
DOI: 10.1111/1756-185x.13047
|View full text |Cite
|
Sign up to set email alerts
|

Gastric antral vascular ectasia in systemic sclerosis: Where do we stand?

Abstract: Gastric antral vascular ectasia (GAVE) continues to be a challenge in both diagnosis and treatment. GAVE has a diverse group of associations and presumed causes, including cirrhosis, chronic renal failure and autoimmune connective tissue diseases. However, in most occasions, the management plan of GAVE itself is the same whatever the underlying disease by using Argon plasma coagulation (APC). Herein, we will discuss three cases of systemic sclerosis-associated GAVE presenting with either acute or chronic gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Despite this association between GAVE and cirrhosis, bleeding from GAVE does not respond to therapy directed at reducing portal blood pressure, suggesting that it may be an immunologic or hormonal phenomenon 8 . GAVE is also associated with chronic kidney disease 1 9 , heart disease 1 10 and autoimmune connective tissue diseases such as systemic sclerosis 9 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite this association between GAVE and cirrhosis, bleeding from GAVE does not respond to therapy directed at reducing portal blood pressure, suggesting that it may be an immunologic or hormonal phenomenon 8 . GAVE is also associated with chronic kidney disease 1 9 , heart disease 1 10 and autoimmune connective tissue diseases such as systemic sclerosis 9 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Autoantibodies are an expression of B-cell hyperactivity promoted by autoreactive T-cells in autoimmune diseases and by donor T-cells in chronic GVHD [ 19 ]. Autoantibodies may cross-react with specific proteins in the gastric mucosa and submucosa leading to inflammation, vascular endothelial cell injury, and ultimately the local release of factors resulting in thrombus formation in these small vessels [ 19 , 20 ]. Additionally, GAVE in scleroderma patients (SSc-GAVE) has been associated with specific antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, GAVE in scleroderma patients (SSc-GAVE) has been associated with specific antibodies. One study demonstrated that patients with SSc-GAVE were positive for anti-RNA polymerase III at a rate of 50% compared to 16% in patients with scleroderma and no evidence of GAVE [ 20 , 21 ]. GAVE lesions in scleroderma have been reported to resolve with immunosuppressive therapy, and gastric biopsies from cases of SSc-GAVE also show CD4+ T-cell infiltration [ 19 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to literature data, the most common cause of erythrocytic system pathology in systemic scle-rosis patients is microcytic anaemia associated with iron deficiency and resulting from relatively common gastrointestinal microhaemorrhages and gastric antral vascular ectasia (GAVE), also known as watermelon stomach, endoscopically characterised by red stripes in the lining [3][4][5].…”
Section: Erythrocyte Abnormalities In Systemic Sclerosismentioning
confidence: 99%